2015
DOI: 10.1038/ajg.2015.153
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of a Digital Rectal Examination Compared With High-Resolution Anorectal Manometry in Patients With Chronic Constipation and Fecal Incontinence

Abstract: DRE shows high sensitivity and positive predictive value in detecting dyssynergia compared with HRAM, and could therefore be used as a bedside screening test for the diagnosis of this disorder. Further studies are warranted to evaluate the correlation between DRE and HRAM in assessing anal sphincter pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 25 publications
(33 reference statements)
5
64
1
3
Order By: Relevance
“…In our study population, type I dyssynergia was seen in 48.6%, type II dyssynergia in 28.4%, type III dyssynergia in 20.8%, and type IV dyssynergia in 2.1% of the patients. These rates are consistent with previous studies [6,41]. The pathogenic mechanisms are different for the different subtypes of DD, and the response to BFT may vary greatly between subtypes.…”
Section: Discussionsupporting
confidence: 81%
“…In our study population, type I dyssynergia was seen in 48.6%, type II dyssynergia in 28.4%, type III dyssynergia in 20.8%, and type IV dyssynergia in 2.1% of the patients. These rates are consistent with previous studies [6,41]. The pathogenic mechanisms are different for the different subtypes of DD, and the response to BFT may vary greatly between subtypes.…”
Section: Discussionsupporting
confidence: 81%
“…Fourth, inherent limitations of the WMC in assessing CTT (ie, due to unidentifiable pH landmarks) or of the HRAM and BET in assessing dyssynergia (ie, due to non-physiological positioning, or abdominal muscle weakness) could have challenged their validity. Such scenarios were noted in our cohort but their impact is difficult to quantify 8 26. It has also been recently shown that although the various HRAM patterns are reproducible, they may be seen in healthy volunteers, questioning its overall utility in functional constipation 6.…”
Section: Discussionmentioning
confidence: 68%
“…However, a digital rectal examination can provide valuable information on the presence of a rectal fecal mass (one of the six diagnostic Rome III criteria for FC) and be helpful in the assessment of anorectal sensation and sphincter tone [16][17][18]. Among the responders of this survey, the vast majority of physicians performed digital rectal examination routinely or occasionally.…”
Section: Diagnostic Work-upmentioning
confidence: 98%